Preliminary Study of How Plea Bargaining Decisions by Prosecution and Defense Attorneys Are Affected - Kathy Pezdek (My University, 2016)
The findings suggest that prosecutors are likely to be amenable to plea bargaining when eyewitness testimony is central to their case, regardless of the circumstances associated with the eyewitness identification (cross-race versus same-race identification or familiarity versus unfamiliarity of eyewitness with the perpetrator); however, prosecutors have sufficient confidence in eyewitness testimony, regardless of the aforementioned factors, so as to remain firm on their initial plea-bargain offer. The study involved a sample of 93 defense attorneys and 46 prosecutors from matched counties in California. The attorneys were presented four scenarios involving eyewitnesses that varied in the following factors: the perpetrator’s race differed from the race of the eyewitness (“cross-race”), the race of the eyewitness was the same as that of the perpetrator, the eyewitness had prior contact with the eyewitness, and the eyewitness had no previous contact with the perpetrator. After reading each scenario, participants were asked five questions regarding their estimate of the probability that the defendant was guilty; the probability that they would win the case if it went to trial; whether they would plea bargain the case; and the lowest/highest plea bargain they would offer/accept. Defense attorneys perceived that the cross-race element of eyewitness evidence favored their client more than the same-race circumstance. Prosecutors were less likely to believe that cross-race identification would weaken their case compared with same-race identification evidence. When the perpetrator was familiar to the eyewitness, prosecutors indicated a higher probability of winning the case at trial. Defense attorneys were less confident of winning the case at trial if the perpetrator had previous contact/familiarity with the perpetrator.